Governance transformed into Corporate Social Responsibility (CSR): New governance innovations in the Canadian oil sands. Issue 2 (April 2016) - Wanvik, Tarje I.
Abstract: In the contested space of energy production in Canada, tension and a series of disputes over land and rights have arisen between the state, industry and local Aboriginal communities. Canadian governments have long exploited the bountiful natural resources of the land, while at the same time attempting to reconcile a difficult relationship with its Aboriginal communities. This case study reveals how the government has yielded responsibility to industry to resolve the many governance challenges of Canada's extractive hot zone. Through substantial delegation of governance duties to industry, the Canadian Government has placed large parts of its regulatory toolbox in the hands of multinational Corporate Social Responsibility (CSR) departments, and hence turned social and environmental planning and programming into corporate stakeholder management. This article sets out to explain these dramatic changes in governance power play and practice by examining the case of the extractive hot zone in Alberta, according to three distinct but interlinked trajectories in governance and CSR scholarship, namely the change from "government" to "governance", the emergence of a claimed post-political condition and the evolution of CSR practices towards stakeholder management.